IMPLICATION OF SPATIAL PATTERN OF HOUSING DISTRIBUTION TO THE EXISTENCE OF AGRICULTURAL LAND IN TABANAN URBAN AREA - Noorwahyuni, Afriyanti; Dwijendra, Ngakan Ketut Acwin; Putra, I Dewa Gede Agung Diasana (ASTONJADRO, 2022)
The Tabanan Urban Area functions as a buffer area (counter magnet) around the Sarbagita Metropolitan core area, namely Denpasar and Kuta. Regional development is directed as a center for government services, trade and services as well as urban settlements. The Tabanan Urban Area is currently the target of expansion of urban housing development, especially those carried out by developers. Most housing developments occur on agricultural land that functions as a buffer for the Balinese ’subak’ cultural order. This study aims to see the implications of the spatial pattern of housing distribution on the existence of agricultural land in the Tabanan Urban Area. This study uses a descriptive qualitative approach with a historical spatial tracking method. Periodization of housing distribution pattern is done by map overlay analysis and nearest neighbor analysis. The findings of this study indicate that the spatial distribution pattern of housing occurs randomly and spreads with a leap-frog development pattern. This form was found to be the most offensive dispersal pattern in reducing existing agricultural land. The implication of this housing distribution pattern on the rate of land conversion was found to reach 40.39 ha or about 33.25% of the Tabanan urban area. Subak, as a subsystem of Balinese cosmic spatial planning, has experienced decadence not only at the physical level, but extends to the systemic socio-religious dimension. The intrusive pattern of Balinese culture and culture occurs due to high land use discrepancies. This is especially true for the three subak subsystems, namely parhayangan-pawongan-palemahan.